Research engagement and career aspirations among public health graduate students: experiences from a developing country - Mohammad Jahid Hasan; Susmita zaman; Salwa Islam; Mohima Benojir Hoque; Jannatul Fardous; Sajia Afrin; Tamanna Tabassum; Mir Paramita Zaman; Md Rafiul Hasan; Masudur Rahman Kanchon; Taha Choudhury; Mohammad Delwer Hossain Hawlader; et al. (BMC Medical Education)
Abstract Background Public health professionals are instrumental in shaping evidence-based policies and improving population health by translating research findings into actionable solutions. To sustain this progress, it is essential to understand the research engagement, aspirations, and challenges of public health students, as their active participation in research is critical for their development into successful public health practitioners. Methods This cross-sectional descriptive study surveyed graduate public health students from universities in Bangladesh offering Master of Public Health program, using a questionnaire to collect data on demographics, research engagement, training, future aspirations, and the challenges encountered during research. Results Among the 417 participating students, the mean age was 31.3 ± 5.7 (SD) years, with a majority being female (58.7%). Approximately half of the participants (49.2%) had engaged in research activities prior to pursuing their current degree, while 27.6% had received formal research training. Of all, 87.8% students (n = 366) had an intention to pursue research career in future. Female students (aOR 2.07, 95% CI 1.02–4.19, p = 0.043), students who were ≥ 30 years (aOR 2.51, 95% CI 1.11–5.69, p = 0.027), and studying MPH in public institutions (aOR 0.45, 95% CI 0.22–0.90, p = 0.024) exhibited a higher likelihood of conducting research independently, compared to male students, age < 30 years and studying MPH in private institutions, respectively. Factors such as prior research training (aOR 5.61, 95% CI 2.64–11.9, p < 0.001) and prior education in non-science discipline (aOR 3.40, 95% CI 1.16–9.99, p = 0.026) were positively associated with conducting research independently. Conclusion Graduate public health students have demonstrated a strong interest in research careers, with nearly half reporting prior research experience. Being able to conduct research independently is shaped by factors such as gender, academic background, and the quality of training they receive.